FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPUASAN PASIEN DIRUANG RAWAT INAP RSD.KH. DAUD ARIF TANJUNG JABUNG BARAT - Faridah Faridah (Universitas Batanghari Jambi, 2015)
The low quality of nursing care of patient expectations not only due to the limited number of nurses , but due to the limited professional skills possessed by most nurses . In addition, socio-economic and social factors of different cultures will also affect the demands of nursing care services , resulting in low quality of nursing care .This research is quantitative research with cross sectional approach to the relationship between the dependent variable and independent variables by means of observation or data collection approach as well . Analysis is conducted multivariate logistic regression analysis were used to examine the relationship of independent variables simultaneously with the dependent variable . Also can be known where the dominant variables associated with the dependent variable . The study sample as many as 87 people , with a random sampling technique samplingOf the 87 respondents there is a relationship between empathy officer with the level of patient satisfaction p value = 0.000 , there is a relationship between physical appearance officer with the level of patient satisfaction p value = 0.005 , there is a security relationship with the level of patient satisfaction p value = 0.019 , there is a relationship between speed officers with patient satisfaction level p value = 0.005 . However, after multivariate analysis test to look for the most dominant factor between the independent variables and the dependent variable showed that the most dominant related to patient satisfaction is the speed of the clerk where p value = 0.000 . Expected management RSD . KH . David Arif can improve the quality of inpatient care in particular with regard to the speed aspect of nurses caring for patientsKeywords : Patient satisfaction level , Hospitalization